2015
DOI: 10.1016/j.nucengdes.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale 3-D finite element modeling of a two-loop pressurized water reactor for heat transfer, thermal–mechanical cyclic stress analysis, and environmental fatigue life estimation

Abstract: This paper discusses a system-level finite element model of a two-loop pressurized water reactor (PWR). Based on this model, system-level heat transfer analysis and subsequent sequentially coupled thermal-mechanical stress analysis were performed for typical thermalmechanical fatigue cycles. The in-air fatigue lives of example components, such as the hot and cold legs, were estimated on the basis of stress analysis results, ASME in-air fatigue life estimation criteria, and fatigue design curves. Furthermore, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…We developed finite element (FE) models for both heat transfer analysis and for subsequent thermal-mechanical stress analysis. In our earlier work [11,12] we presented a preliminary/skeletal FE model of an overall reactor consisting of a reactor pressure vessel, hot leg, cold leg, and steam generator. In this work, we present a detailed FE model of the reactor pressure vessel and its nozzle only.…”
Section: Finite Element Model Of Reactor Pressure Vessel and Nozzlesmentioning
confidence: 99%
See 4 more Smart Citations
“…We developed finite element (FE) models for both heat transfer analysis and for subsequent thermal-mechanical stress analysis. In our earlier work [11,12] we presented a preliminary/skeletal FE model of an overall reactor consisting of a reactor pressure vessel, hot leg, cold leg, and steam generator. In this work, we present a detailed FE model of the reactor pressure vessel and its nozzle only.…”
Section: Finite Element Model Of Reactor Pressure Vessel and Nozzlesmentioning
confidence: 99%
“…For the requirement of modeling cracks, 3D models were developed and meshed by using eight nodded 3D brick elements. In our previous work [11,12] we found that eight-node linear elements (DC3D8) were sufficient to model heat transfer compared to a computationally expensive counterpart of 20-node brick elements (DC3D10). For stress analysis, the corresponding C3D8, 8-node linear elements were used.…”
Section: Finite Element Model Of Reactor Pressure Vessel and Nozzlesmentioning
confidence: 99%
See 3 more Smart Citations